Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content:1. The reality of organizational isolation in the public sector in Saudi ArabiaMrs. Hussah Mohammed Alareifi, Dr. Najla Ibrahim Alshenaifi2. The effect of global energy price fluctuations on oil derivative prices and domestic prices in Jordan: GARCH modelMrs. Saba Bassam Al-Damour, Co-Prof. Radi Mohammad Adailah, Co-Prof. Ahmad Abedalqader Al-Majali3. The mediating role of service adequacy in the relationship between follow-up and evaluation  and service quality  "Case study on commercial banks – Sudan – Elobied"Co-Prof. Mostafa Adam Mohammed, Asst-Prof. Adam Yagoub Abker, Co-Prof. Abdelaziz Hassan Abdelaziz4. The reality of Sustainable Leadership practice: An exploratory study on King Saud University During the period January to February of 2023Mrs. Majd Talal Alamri, Prof. Khalid Mohammed Alaiban5. Online Arbitration for the Settlement of Disputes in the Contracts of Electronic CommerceMrs. Renad Abdulkarim Alseadoon, Mr. Abdulkarim Mohammad Alseadoon , Dr. Mohammad Abdastar Abdulwhab6. The effect of work environment conditions on the performance of workers in Lebanese private hospitals during the Lebanese financial crisis: The case of private hospitals in North LebanonMr. Ghassan Fawaz Fathallah, Co-Prof. Khaled Kamal-El-Din7. The added value of internal auditing in reducing creative accounting practicesDr. Mozamil Awad Taha
Keywords: Journal of Economic, Administrative and Legal Sciences